(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2023)
The rapid shift to online teaching and learning during the COVID-19 pandemic required lecturers to think of altering their pedagogical approaches to suit online learning. One of those pedagogical approaches is fostering student engagement. We are two teacher educators who collaborated using a self-study methodology to look into our practice to learn about fostering student engagement in an online teaching environment. This study was guided by the theory of experiential learning and collaboration. Data were collected from our journal entries and collaboration discussions to narrate how our collaborative endeavours enabled us to learn about fostering student engagement in an online teaching platform. While the findings of what we learnt about fostering student engagement when teaching online are not entirely new in literature, we found that our collaborative endeavours helped us to deal with our fears and vulnerabilities as well as noticing pertinent aspects of student engagement in online teaching. We recommend that lecturers need to embrace collaboration in negotiating new and challenging educational situations.